Transit Housing as A Model For Islamic Education Environments For Non-Resident Students at the Nurul Islam Karangcempaka Bluto Sumenep Islamic Boarding School - Emna Laisa; Nihayatur Rahmah; Firdausiyah Firdausiyah; Sri Ira Suharwati; Masti Yanto; Nailatur Rizqiyah (Pascasarjana IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the role of a transit dormitory (pondok transit) as a model of the Islamic Religious Education environment for non-resident students at Nurul Islam Islamic Boarding School, Karangcempaka Bluto, Sumenep. This research employed a qualitative approach using a case study design to gain an in-depth understanding of the educational practices taking place within the transit dormitory environment. Data were collected through observation, in-depth interviews with pesantren caregivers, teachers, and students, as well as documentation of educational activities conducted in the transit dormitory. Data analysis was carried out through the processes of data reduction, data display, and interpretative conclusion drawing. The findings reveal that the transit dormitory functions as an educational transition space bridging formal education in madrasah and Qur’anic learning in pesantren institutions. Its presence not only fulfills students’ physical needs, such as meals, rest, and a safe environment, but also serves as a medium for spiritual development through congregational prayers, Qur’an recitation, and memorization review activities. Furthermore, the transit dormitory contributes to the development of religious character, discipline, and social cohesion among students through structured religious routines and social interactions. This study formulates a model of an Islamic educational environment based on the transit dormitory that integrates physical, spiritual, and academic dimensions in a holistic and sustainable framework for non-resident students.